Pemberdayaan Ekonomi Masyarakat Pesisir (PEMP) : Suatu Kajian di Kecamatan Cilincing, Jakarta Utara - Dara Aisyah; Katiman Rostam; Abd Hair Awang; Ambar Teguh Sulistyani (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2009)
This paper discusses empowerment program for coastal communities in Cilincing district, North Jakarta. Basically, the program has bees relatively successful in developing coastal communities's entrepreneurship. This can be seen from the estabilishment of cooperatives and small scale enterprises in that area. But, this paper underlines that grant allocation for the fisherman is still limited. Otherwise, the merchants received the most amount of grant allocation. In other word, bias on delivering program has occurred. Furthermore, target location for this program has not been equal yet.It was concentrated on few villages only low understanding for loan scheme also became crucial problem for the program. This has pushed for bad credit in a lot of amount.